Kratom Abuse in Ramathibodi Poison Center, Thailand: A Five-Year Experience - Satariya Trakulsrichai (2018)
Kratom (Mitragyna speciosa Korth), a native tree in Southeast Asia, is misused as an abuse drug and becomes legally widespread to several countries. Currently, it is available through the online market or by some shops. The clinical manifestations of Kratom's effects are not well-defined and the clinical studies are limited. This study was designed to identify the characteristics of Kratom poisoning and withdrawal cases from Kratom exposure cases in Ramathibodi Poison Center (RPC), Thailand, during a five-year period. We used a retrospective review of Kratom exposure cases from the RPC toxic surveillance system. A total of 52 Kratom exposure cases were identified. The trend of case consultations has been increasing. There were Kratom poisoning cases (76.9%) and withdrawal cases (23.1%). Common presenting symptoms in the poisoning group were palpitation (22.5%), followed by seizure (17.5%). For the withdrawal group, the common presenting symptoms were myalgia (33.3%), insomnia (16.67%), fatigue (16.67%), and chest discomfort (16.67%). There was a baby with withdrawal symptoms who was delivered from a chronic Kratom-abusing mother, suggesting possible exposure via the transplacental route. There were no deaths in either group. Kratom abuse can cause either poisoning or withdrawal. Most cases in both groups had good prognostic outcome. © 2013 Taylor and Francis Group, LLC.